2021
DOI: 10.3390/ani11092596
|View full text |Cite
|
Sign up to set email alerts
|

RNA Profiles of the Korat Chicken Breast Muscle with Increased Carnosine Content Produced through Dietary Supplementation with β-Alanine or L-Histidine

Abstract: Korat chicken (KRC) is a slow-growing chicken bred in Thailand, whose meat exhibits a unique toughness. A previous study produced KRC breast meat containing high carnosine content through dietary supplementation with β-alanine or L-histidine; however, the KRC that were fed an L-histidine-supplemented diet produced meat that was significantly more tender. Herein, we performed RNA-Seq to identify candidate genes involved in the regulation of carnosine content and meat toughness. Total RNA was isolated from five … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 60 publications
(75 reference statements)
0
4
0
Order By: Relevance
“… Katemala et al (2021) reported that the β-sheet relative content positively correlated with the shear force of KRC, and the result was confirmed by Beattie et al (2004) . Moreover, Kubota et al (2021) found that the upregulated genes LOC107051274, ACSBG1 , and CAPNS2 and downregulated genes MYO7B, MYBPH, SERPINH1 , and PGAM1 may be related to meat tenderness in Korat chicken. However, it is still unclear how these genes change the protein secondary structure in this study.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“… Katemala et al (2021) reported that the β-sheet relative content positively correlated with the shear force of KRC, and the result was confirmed by Beattie et al (2004) . Moreover, Kubota et al (2021) found that the upregulated genes LOC107051274, ACSBG1 , and CAPNS2 and downregulated genes MYO7B, MYBPH, SERPINH1 , and PGAM1 may be related to meat tenderness in Korat chicken. However, it is still unclear how these genes change the protein secondary structure in this study.…”
Section: Resultsmentioning
confidence: 97%
“…The 4 experimental diets, all of which were formulated based on the National Research Council nutrient recommendations (1994), were as follows: basal diet (A), basal diet supplemented with 1.0% β-alanine (B), 0.5% L-histidine (C), and 1.0% β-alanine combined with 0.5% L-histidine (D). The ingredient and nutrient compositions of the experimental diet for growers (22–42 days) and finishers (43–70 days) are shown in Table 1 , some of which have already been published by Kubota et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
“…Studies have pointed out that white streaks and lignified chicken breasts in broiler breasts may be related to LDHA , but no causal relationship has been established ( Malila et al, 2019 ). Phosphoglycerate mutase 1 ( PGAM1 ) may be a potential molecular marker of chicken tenderness, and its expression is positively correlated with broiler breast muscle shear stress ( Kubota et al, 2021 ). Fructose bisphosphatase 2 ( FBP2 ) can promote fetal birth weight, and is positively correlated with the development of middle and late skeletal muscle in sheep ( Xu et al, 2014 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PEPT1 gene is a member of the POT family of membrane transporters that uses the proton electrochemical gradient to drive the uptake of di-and tripeptides across cell membranes [90], and is therefore capable of transporting both L-histidine and carnosine in skeletal muscle [14]. Kubota et al (2021) [91] analyzed the RNA profile of Korat chicken supplemented with β-alanine and L-histidine, which resulted in a very tender breast muscle. The authors noted increased expression of genes involved in the regulation of myosin, intramuscular fat and calpain (LOC107051274, ACSBG1, and CAPNS2) and decreased expression of myosin VIIB (MYO7B), myosin binding protein H (MYBPH), inhibitor of serpin peptidase H (SERPINH1) and phosphoglycerate mutase 1 (PGAM1) genes.…”
Section: Amino Acidsmentioning
confidence: 99%